Remarks of Fixed Point for (ψ,φ)-Weakly Contractive Mappings - Zhiqun Xue; Guiwen Lv (Journal of Mathematics)
In this paper, we obtain a new fixed point theorem for weak contraction mappings on complete generalized metric spaces. Our result is different from that of (ψ,φ)-weakly contractive mappings which had been obtained by Lakzian–Samet’s [Appl. Math. Lett. 25 (2012) 902–906]. Moreover, an example is given to illustrate the usability of the obtained result.